2015
DOI: 10.1016/j.expneurol.2015.08.002
|View full text |Cite
|
Sign up to set email alerts
|

Studying polyglutamine diseases in Drosophila

Abstract: Polyglutamine (polyQ) diseases are a family of dominantly transmitted neurodegenerative disorders caused by an abnormal expansion of CAG trinucleotide repeats in the protein-coding regions of the respective disease-causing genes. Despite their simple genetic basis, the etiology of these diseases is far from clear. Over the past two decades, Drosophila has proven to be successful in modeling this family of neurodegenerative disorders, including the faithful recapitulation of pathological features such as polyQ … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
22
0
3

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 288 publications
2
22
0
3
Order By: Relevance
“…Eye-specific expression of Huntingtin-polyQ polypeptides (HTT.Q93) results in neuronal degeneration reflected by depigmentation of the adult eye (Figure 6F,I, Supplemental Table 2) as previously shown (Xu et al, 2015). This depigmentation phenotype is suppressed by knockdown of the Nil phosphatase (Figure 6G,J, Supplemental Table 2) but only marginally altered by overexpression of PPM1B, the human homolog of Nil, (Figure 6H,K, Supplemental Table 2).…”
Section: Phosphorylation Of Acn Serine 437 In Nil 1 Animal Elevates Basal Autophagysupporting
confidence: 70%
“…Eye-specific expression of Huntingtin-polyQ polypeptides (HTT.Q93) results in neuronal degeneration reflected by depigmentation of the adult eye (Figure 6F,I, Supplemental Table 2) as previously shown (Xu et al, 2015). This depigmentation phenotype is suppressed by knockdown of the Nil phosphatase (Figure 6G,J, Supplemental Table 2) but only marginally altered by overexpression of PPM1B, the human homolog of Nil, (Figure 6H,K, Supplemental Table 2).…”
Section: Phosphorylation Of Acn Serine 437 In Nil 1 Animal Elevates Basal Autophagysupporting
confidence: 70%
“…Then, the publication of the first annotated version of Drosophila genomic sequence (Myers et al, 2000 ) confirmed that many human genes involved in all kinds of human diseases had an ortholog counterpart in the fly (Reiter et al, 2001 ). Moreover, genetic manipulation of those genes has successfully led to molecular, biochemical, tissue and behavioral defects that mirror the human conditions (Botella et al, 2009 ; Bouleau and Tricoire, 2015 ; Casci and Pandey, 2015 ; Xu et al, 2015 ). A remarkable example is the discovery of the molecular basis of behavior by characterization of genes controlling circadian rhythm and the biological clock (Konopka and Benzer, 1971 ).…”
Section: Introductionmentioning
confidence: 99%
“…Genetic and molecular studies in Drosophila can provide valuable insight into the pathogenesis of human diseases, due to the high conservation of key molecular mechanisms underlying biological processes in metazoans, and to the fact that about 77% human disease genes have orthologues in Drosophila [ 1 ]. Thus, targeted expression of mutant human disease genes in Drosophila can recapitulate relevant aspects of the pathology [ 2 , 3 ]. Such expression is frequently achieved by employing the binary Gal4/UAS system, which allows the control of the activity of the gene of interest in a spatiotemporal-restricted manner [ 4 ].…”
Section: Introductionmentioning
confidence: 99%